EP382/#1139 Effect of bleeding disorders on perioperative hysterectomy transfusions: a national surgical quality improvement program (NSQIP) study. (4th December 2022) - Lee, Sarah; Pothuri, Bhavana
Abstract : Objectives: Perioperative management varies for patients with bleeding disorders. We sought to determine the association between bleeding disorders and perioperative transfusions for hysterectomy patients. Methods: We included patients undergoing non-emergent hysterectomy between 2014–2019 from the NSQIP, a validated, risk-adjusted database from 700 hospitals. We compared 30-day perioperative transfusions between patients with and without bleeding disorders (chronic, persistent, active hematologic disorders). Transfusions ≤1day were immediate, and after ≥2days were delayed. Covariates were age, race/ethnicity, preoperative anemia (hematocrit <=30%) and thrombocytopenia (platelet <100, 000/mL), fibroids, endometriosis, cancer, and surgical route. Results: Of 290, 642 patients, 10, 705 (3.7%) received perioperative transfusions (8, 679, 2.9%, immediate; 2, 026, 0.7%, delayed). Of 2, 687 patients with bleeding disorders, 283 (10.5%) received transfusions, compared to 10, 422/287, 995 (3.6%) of those without (p<0.001). For gynecologic cancer patients, 17.1% (121/707) with bleeding disorders received transfusions compared to 8.4% (3, 261/38, 379) of those without (p<0.001). 999 (0.3%) underwent reoperation for bleeding, and this was more likely with bleeding disorders (27/2, 687, 1.0% vs. 972/287, 955, 0.3%, p<0.001). Anemia (OR 11.7, CI 11.1–12.4) and bleeding disorders (OR 2.0, CI 1.7–2.3) were associated with transfusions when adjusting for age, race/ethnicity, fibroids, endometriosis, cancer, and surgical approach. The effect of bleeding disorders on transfusions persisted in the laparoscopic group (OR 2.5, CI 1.9–3.3). Bleeding disorders were associated with immediate transfusions (OR 1.7, CI 1.5–2.0) and delayed transfusions (OR 2.1, CI 1.6–2.7). Conclusions: Patients with bleeding disorders are twice as likely to receive immediate and delayed transfusions for hysterectomies, even with a laparoscopic approach. Data are needed to optimize bleeding disorders to decrease transfusion risk.